PERANCANG SISTEM PAKAR DIAGNOSIS KERUSAKAN PERANGKAT KERAS MENGGUNAKAN POHON KEPUTUSAN - Nursafitri Meylani Pane; Mochammad Sisin Saiful Umam; Fitriani Noor Fauziah (Universitas Methodist Indonesia, 2020)
The development of computer technology is also followed by the increasing number of computer users in the world. Along with the increasing number of computer users, the problem of computer damage has become quite a complicated problem. This is understandable considering the number of computer users who lack knowledge about computers, especially in dealing with computer damage. In addition, the limited memory and knowledge of a technician about computer damage can cause errors or inaccuracies in diagnosing the damage. In designing this system the approach method used is structured oriented with the system development method used is a prototype model. The supporting software used to design a food menu ordering information system is Power Designer, Bizagi Modeler, Balsamiq, and Microsoft Visio. The final result of this activity is in the form of an expert system design report to diagnose web-based hardware damage. With the expert system created, it is expected to be able to overcome errors in determining damage caused by the limited memory of technicians.